Democracy's diversity and flexibility as an ideal In the Arab world and the impact of Islam as a religion (Journal of the College of Basic Education, 2022)
Democracy is not just a piece of paper thrown into the ballot boxes, or a seat occupied by the elected representative under the dome of parliament. Rather, democracy is principles embodied in freedom and equality, which are constitutional guarantees that affirm the principle of the sovereignty of the nation and its being the source of all powers and the holder of jurisdiction over itself.Democracy arose in ancient Europe and in Athens (Greece) now, specifically in the period between 700-500 BC, and Athens emerged and reached its peak of prosperity in the fifth century BC, where Athens followed a democratic system based on citizenship that serves the interest of the majority and guarantees equality before the law. There were many and varied forms of democracy, and through what was agreed upon by the jurists, it was divided into three main forms, and the focus was on the concept of representative democracy based on participation and which is based on the principle of agency.